PENGARUH KOMPETENSI DAN SUPERVISI TERHADAP KINERJA GURU DENGAN MOTIVASI SEBAGAI MEDIASI (Studi Kasus pada Guru SD Dabin VI,VII,VIII UPT Dinas Pendidikan Kecamatan Rembang) - Sudaryono, 12.5202.0056; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of competence and supervision of the performance of the motivation as mediation (Studies in the District Education Office Apex UPT). The population in this study is that there are teachers in the target areas 6,7 , and 8, the District Education Office Apex UPT number of 119 teachers . Using census sampling method , ie all members of the population sampled . Mechanical testing data used include test descriptions , test validity , reliability testing , test models that include test and F-test coefficient of determination , which includes the classical assumption of normality test , test and test heteroskedasitas multicollinearity , test hypotheses and tests of mediation. Research shows that the ability of the model to correctly describe the effect of variable competence , supervision and motivation is at 66.1 % of the performance . While others of 33.9 % is explained by variables outside the model . From the test results it can be seen that the mediating effects of motivation did not mediate the effect of proven competence and supervision of the performance . Keywords : competence , supervision , motivation and performance.